Integrated farming system in India: Current status, scope and future prospects in changing agricultural scenario - KUMAR, SANJEEV; BHATT, B P; DEY, A; SHIVANI, SHIVANI; KUMAR, UJJWAL; IDRIS, MD; MISHRA, J S; KUMAR, SANTOSH (The Indian Journal of Agricultural Sciences, 2018)
Small and marginal farmers are the core of the Indian rural economy constituting 85% of the total farming community but possessing only 44% of the total operational land. Indian agriculture is labour oriented and requires lot of man-power and energy but even after this hard work farmers are not in a position to earn their livelihood, especially small farmers because there is very little left after they pay for all inputs (seeds, livestock breeds, fertilizers, pesticides, energy, feed, labour, etc.). To fulfill basic needs of these farm families including food (cereal, pulses, oilseeds, milk, fruit, honey, meat etc.), feed fodder, fibre and fuel warrant an attention about integrated farming system (IFS). The emergence of IFS has enabled us to develop a framework for an alternative development model to improve the feasibility of small sized farming operations in relation to larger ones. IFS refer to agricultural systems that integrate livestock and crop production or integrate fish and livestock and may sometimes be known as integrated bio systems. In this system, an inter-related set of enterprises are used so that the waste from one component becomes an input for other enterprises of the system, which reduces cost and improves production and thereby income. Integrated farming systems seem to be the possible solution to the continuous increase of demand for food and nutrition, income stability and livelihood upliftment particularly for small and marginal farmers with little resources. Based on the research works conducted all over the country, it is clear that crop cultivation alone can’t fulfill the demand of food and nutritional requirement and we have to focus on multi-component farming as it is the only way of efficient resource recycling within the system with increased economic profitability, economic stability, enhanced soil sustainability, and preserving environmental quality and maintaining biological diversity and ecological stability.